Airborne fallout measurements in India - VOHRA, K. G.; RANGARAJAN, C.; INGLE, N. A. (MAUSAM, 1960)
Studies on the radioactive contamination of the surface air by fallout from the testing of nuclear weapons have been carried out in India at the Atomic Energy Establishment, Trombay, since early 1956. These studies have been found to provide a general indication of the intensity of world-wide fallout in India following the different series of bomb testing. The variations in the fall-out content of the surface air depend not only on the pattern of bomb testing but also on the meteorological factors such as rainfall, winds etc. This report presents seasonal variations as well as monthly variations in the airborne fallout activity at the different sampling stations.